Missense Variants in the Histone Acetyltransferase Complex Component Gene TRRAP Cause Autism and Syndromic Intellectual Disability. - Cogné, Benjamin; Ehresmann, Sophie; Beauregard-Lacroix, Eliane; Rousseau, Justine; Besnard, Thomas; Garcia, Thomas; Petrovski, Slavé; Avni, Shiri; McWalter, Kirsty; Blackburn, Patrick R; Sanders, Stephan J; Uguen, Kévin; et al. (Am J Hum Genet, 2019)
Acetylation of the lysine residues in histones and other DNA-binding proteins plays a major role in regulation of eukaryotic gene expression. This process is controlled by histone acetyltransferases (HATs/KATs) found in multiprotein complexes that are recruited to chromatin by the scaffolding subunit transformation/transcription domain-associated protein (TRRAP). TRRAP is evolutionarily conserved and is among the top five genes intolerant to missense variation. Through an international collaboration, 17 distinct de novo or apparently de novo variants were identified in TRRAP in 24 individuals. A strong genotype-phenotype correlation was observed with two distinct clinical spectra. The first is a complex, multi-systemic syndrome associated with various malformations of the brain, heart, kidneys, and genitourinary system and characterized by a wide range of intellectual functioning; a number of affected individuals have intellectual disability (ID) and markedly impaired basic life functions. Individuals with this phenotype had missense variants clustering around the c.3127G>A p.(Ala1043Thr) variant identified in five individuals. The second spectrum manifested with autism spectrum disorder (ASD) and/or ID and epilepsy. Facial dysmorphism was seen in both groups and included upslanted palpebral fissures, epicanthus, telecanthus, a wide nasal bridge and ridge, a broad and smooth philtrum, and a thin upper lip. RNA sequencing analysis of skin fibroblasts derived from affected individuals skin fibroblasts showed significant changes in the expression of several genes implicated in neuronal function and ion transport. Thus, we describe here the clinical spectrum associated with TRRAP pathogenic missense variants, and we suggest a genotype-phenotype correlation useful for clinical evaluation of the pathogenicity of the variants.

De Novo Disruption of the Proteasome Regulatory Subunit PSMD12 Causes a Syndromic Neurodevelopmental Disorder. - Küry, Sébastien; Besnard, Thomas; Ebstein, Frédéric; Khan, Tahir N; Gambin, Tomasz; Douglas, Jessica; Bacino, Carlos A; Craigen, William J; Sanders, Stephan J; Lehmann, Andrea; Latypova, Xénia; Khan, Kamal; et al. (Am J Hum Genet, 2017)
Degradation of proteins by the ubiquitin-proteasome system (UPS) is an essential biological process in the development of eukaryotic organisms. Dysregulation of this mechanism leads to numerous human neurodegenerative or neurodevelopmental disorders. Through a multi-center collaboration, we identified six de novo genomic deletions and four de novo point mutations involving PSMD12, encoding the non-ATPase subunit PSMD12 (aka RPN5) of the 19S regulator of 26S proteasome complex, in unrelated individuals with intellectual disability, congenital malformations, ophthalmologic anomalies, feeding difficulties, deafness, and subtle dysmorphic facial features. We observed reduced PSMD12 levels and an accumulation of ubiquitinated proteins without any impairment of proteasome catalytic activity. Our PSMD12 loss-of-function zebrafish CRISPR/Cas9 model exhibited microcephaly, decreased convolution of the renal tubules, and abnormal craniofacial morphology. Our data support the biological importance of PSMD12 as a scaffolding subunit in proteasome function during development and neurogenesis in particular; they enable the definition of a neurodevelopmental disorder due to PSMD12 variants, expanding the phenotypic spectrum of UPS-dependent disorders.
Keywords: Adolescent; Animals; Child; Child, Preschool; Disease Models, Animal; DNA Copy Number Variations; Down-Regulation; Female; Gene Deletion; Humans; Infant; Intellectual Disability; Male; Microcephaly; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Proteasome Endopeptidase Complex; Zebrafish